Sistemas estruturais em formato de abóbada reticulada - Ferreira, Núbia dos Santos Saad (2012)
The structural systems with reticulated vault shape are concave structures, having a diamond or triangular shape and capable of generating light roofs designed to overcome large spans. They have a favorable geometric shape to receive and distribute loads, with predominant axial efforts. They have a remarkable technical and economic viability, since they allow rational use of materials, promoting the industrialization of buildings, with the use of prefabricated spare parts and they also have small nodal displacements. The vault historical evolution followed the technological advances of structural materials (masonry, concrete, steel, glued laminated wood). Significant achievements are worldwide listed which proves its efficient structural behavior. This kind of structure, however, is not normally employed in Brazil and, in this way, this work aims to present the technical characteristics and design methodologies with particular interest in the use of wood being justified by economic, environmental and social factors. We conducted a sensitivity analysis for lamellar vault systems using experimental planning techniques, response surface and Taguchi Methodology. From this study, we measured the structural behavior variations regarding active efforts on the bars (axial force and bending moments) and overall structure nodal displacements by significant disturbances occurred in the intervening variables. The results show that the span is the design variable of greater influence on the effort values, having the lamella height as the highest impact caused onto the nodal displacements. In addition, a methodology to obtain the response surfaces was implemented. It considers security checks for ultimate limit states and use based on the Brazilian standard NBR 7190 Timber structures design, which are intended to assist in calculating the design of structures with optimal values for design variables. The results showed that this structural systems have all the advantages with wood materials and a reliable system for design and construction of vault timber structures in Brazil.